Volatile Signals From Guava Plants Prime Defense Signaling and Increase Jasmonate-Dependent Herbivore Resistance in Neighboring Citrus Plants - Ling, Siquan; Rizvi, Syed Arif Hussain; Xiong, Ting; Liu, Jiali; Gu, Yanping; Wang, Siwei; Zeng, Xinnian (Frontiers in Plant Science, 2022)
Intercropping can reduce agricultural pest incidence and represents an important sustainable alternative to conventional pest control methods. Citrus intercropped with guava (Psidium guajava L.) has a lower incidence of Asian citrus psyllid (ACP, Diaphorina citri Kuwayama) and huanglongbing disease (HLB), but the mechanisms are still not well understood. In this study, whether volatile organic compounds (VOCs) emitted from guava plants play a role in plant–plant communications and trigger defense responses in sweet orange (Citrus sinensis (L.) Osbeck) was tested in the laboratory. The results showed that the behavioral preference and developmental performance of ACP on citrus plants that were exposed to guava VOCs were suppressed. The expression of defense-related pathways involved in early signaling, jasmonate (JA) biosynthesis, and protease inhibitor (PI), terpenoid, phenylpropanoid, and flavonoid biosynthesis was induced in guava VOC-exposed citrus plants. Headspace analysis showed that guava plants constitutively emit high levels of (E)-β-caryophyllene and (E)-4,8-dimethyl-1,3,7-nonatriene (DMNT), which can induce the accumulation of JA and promote stronger defense responses of citrus to ACP feeding. In addition, exposure to guava VOCs also increased the indirect defense of citrus by attracting the parasitic wasp Tamarixia radiata. Together, our findings indicate that citrus plants can eavesdrop on the VOC cues emitted from neighboring intact guava plants to boost their JA-dependent anti-herbivore activities. Knowledge from this study may lead to a mechanism of citrus-guava intercropping for the ecological management of insect pests.